2020
DOI: 10.1016/j.conbuildmat.2020.119043
|View full text |Cite
|
Sign up to set email alerts
|

Durability of hemp concretes exposed to accelerated environmental aging

Abstract: This study examines the evolution of the functional properties of two hemp concretes formulated with two different binders over 2 years in different environmental conditions. Stable environmental conditions (50% RH -20°C) have been applied to hemp concretes to obtain the reference aging A REF .An accelerated aging process A WD is chosen, consisting of cycles of wetting and drying. In relation to the reference aging, no significant variation of the chemical, microstructural and functional properties is observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Despite the long duration of this type of aging, we did not observe significant changes in the properties of the material after aging. These results are in line with the literature where authors have concluded that microstructural changes are not sufficient to lead to modifications in material properties during the first months of aging [27,28].…”
Section: Methodssupporting
confidence: 92%
“…Despite the long duration of this type of aging, we did not observe significant changes in the properties of the material after aging. These results are in line with the literature where authors have concluded that microstructural changes are not sufficient to lead to modifications in material properties during the first months of aging [27,28].…”
Section: Methodssupporting
confidence: 92%
“…− 𝜆 𝛻𝑇 − 𝜌 𝑙 𝐿 𝑣 𝐷 𝑇,𝑣 𝛻𝑇 + 𝜌 𝑙 𝐿 𝑣 𝐷 𝜃,𝑣 𝛻𝜃 = ℎ 𝑇,L,0 (𝑇 𝑎,𝑒,𝑖 − 𝑇 𝑠,𝑒,𝑖 ) + 𝜌 𝑙 𝐿 𝑣 (𝜌𝑣 𝑎,𝑒,𝑖 − 𝜌𝑣 𝑠,𝑒,𝑖 ) + 𝜑 𝑟𝑎𝑑,𝑒,𝑖 (4) Where hT,L,0 is the convective heat transfer coefficient from external and internal sides, ρv,e,i is the air density, and φrad,e,i is a radiation term which is assumed negligible in our study.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The scientific community carried out several work in order to demonstrate the thermal and hygroscopic efficiency of bio-based material compared to classical insulation materials, and the advantages they offer in terms of energy needs [1], environmental impact [2], indoor air quality, durability [3], [4], [5], and thermal comfort [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are two common ways of aging of building materials-artificial accelerated aging (hereinafter referred to as 'artificial aging') and natural environmental aging (hereinafter termed as 'natural aging') [7]-with various specific methods and standards. Artificial aging involves simulating a certain temperature [8,9], humidity [10,11], drying-wetting changes [12,13], freeze-thaw cycles [14], ultraviolet radiations [15], and other conditions in the aging test box based on the characteristics of the service life environment of the studied material and the characteristics of the material itself. Natural aging is mostly to place the test specimen in a typical service life environment for a certain period to allow it to accept the aging effect of the environment that is most in line with the actual state to evaluate the material durability [16].…”
Section: Introductionmentioning
confidence: 99%